WCF 4.0 multi-tier services development with LINQ to Entities : build SOA applications on the Microsoft platform with this hands-on guide updated for VS2010 /: build SOA applications on the Microsoft platform with this hands-on guide updated for VS2010. (2010) - Unknown
No abstract available